Family medicine teachers’ profile: selection criteria (workshop) - dos Santos Ferreira, Ana Cristina (2024)
The growing number of Family Medicine Teachers in Portugal increases training capacity, which is not accompanied by a higher placement of medical residents in some geographic locations. Thus, it is necessary to establish local selection criteria that guarantee fairness and transparency in the process of allocating positions for new residents. To discuss this topic among clinical teachers, a workshop was held during the ARSLVT Family Medicine Teachers Open Day, on May 2023. Participants were asked to select the characteristics they valued most through a collaborative reflection process and participatory methodologies. They suggested some objective systems for ranking criteria that could be applied to the clinical teacher, the health unit, and the welcoming team. It was concluded that developing consensual criteria is challenging, as their appreciation is subjective and stems from personal past experiences and the local reality.